Design Techniques for Spectral Quantization in Wideband Speech Coding - Biundo, Giuseppina; Grassi, Sara; Ansorge, Michael; Pellandini, Fausto; Farine, Pierre-André (My University, 2002)
In this paper we describe the design of spectral quantization for wideband speech coding in order to achieve low bit-rate, low-complexity, transparent quantization schemes. The theoretical bases are given as well as the experimental design, listening tests and the implementation in a proprietary CELP (Code Excited Linear Prediction) coder.